SSR 마커를 이용한 배 유전자원의 유연관계 - 천재안(Jae An Chun); 조강희(Kang Hee Cho); 김세희(Se Hee Kim); 이한찬(Han-chan Lee); 최인명(In Myong Choi); 박서준(Seo Jun (Journal of plant biotechnology, 2016)
This study analyzed the genetic diversity of 115 pear germplasms using 15 SSR markers. Three to forty-one SSR alleles were detected for each locus with an average of 16 alleles per locus. The average availability of markers was 0.966. The average observed heterozygosity ($H_{obs}$) was 0.603 (range: 0.140 to 0.929). The average expected heterozygosity ($H_{exp}$) was 0.718 (range: 0.463 to 0.904). The average polymorphism information content (PIC) was 0.692 (range: 0.403 to 0.897). The genetic relationships of pear germplasms were classified into two major groups by geographic origins and genetic characteristics according to genetic distance. The first group was composed of European pear belonging to Pyrus communis. The second group consisted of P. pyrifolia, P. ussuriensis, P. bretschneideri, P. betulaefolia, P. calleryana, interspecific hybrids, and unclear germplasms. The results of this study suggest that genotype analysis of pear germplasms using SSR markers can identify the genetic diversity of germplasms, and can be used to provide basic information for pear breeding. 본 연구는 15개의 SSR 마커를 이용하여 배 유전자원 115점에 대한 유전적 다양성을 분석하였다. 분석된 마커당 대립유전자수는 3 ~ 41개로 평균 16개였으며, 마커의 이용도는 평균 0.966이었다. $H_{obs}$는 0.140 ~ 0.929로 평균 0.603이었으며 $H_{exp}$는 0.463~0.904로 평균 0.718로 분석되었다. PIC 값은 0.403 ~ 0.897의 범위에 속하였으며 평균값은 0.692 이었다. 배 유전자원의 유전적 거리에 따라 계통간 유연관계를 분석한 결과 지리적 분포와 유전적 특성에 의해 크게 2개의 그룹으로 구분되었다. 첫 번째 그룹은 유럽종 P. communis에 속하는 품종으로 구성되었으며 두 번째 그룹은 동양배 그룹으로 P. pyrifolia, P. ussuriensis, P. bretschneideri, P. betulaefolia, P. calleryana와 교잡종 및 종의 분류가 명확하지 않은 유전자원이 포함되었다. 본 연구는 배 유전자원의 유전자형 분석을 통하여 유전적 다양성을 가지는 품종들을 분류하였으며, 육종을 위한 기초자료로 활용 가능할 것으로 사료된다.